Pengembangan Sistem Informasi Distribusi Parking Stand Berbasis Web untuk Mengurangi Risiko Kesalahan Komunikasi Antar Unit Operasional Bandar Udara Yogyakarta Internasional - Farsya Meidiana Zahra; Tata Sumitra; Iswandir; Muryan Awaludin Awaludin (Jurnal Mahasiswa Informatika dan Desain, 2026)
The Apron Movement Control (AMC) unit at Yogyakarta International Airport currently communicates parking stand allocation and changes to ATC officers through conventional, poorly documented communication channels, complicating schedule revision tracking and potentially disrupting take-off/landing punctuality. This study developed a website-based parking stand planning information system with a client-server architecture using PHP and MySQL. The research method used a comparative quantitative approach, comparing 50 communication data samples before and after system implementation. The results showed that the average information distribution time decreased drastically from 10.2 minutes to 1.8 minutes (82.4% efficiency). The error rate in reading parking stand data by ATC officers decreased from 16% to 1.2%. The accuracy of recorded historical parking stand change data reached 99.8%, compared to the manual system which only reached 78.5% due to a lot of scattered data. This system also succeeded in reducing the average processing time for daily parking stand reports from 30 minutes to 3 minutes (90% efficiency). Thus, the implementation of this web-based information system has proven effective in accelerating the flow of information, increasing data accuracy, and supporting flight operational safety at Yogyakarta International Airport.